The Influences of Cyber Extension and Communication Media (Facebook, WhatsApp, Youtube) on Innovation Adoption in Nganjuk Regency - Rini Purwiyati; Ahsin Daroini; Abu Talkah (HABITAT, 2020)
Agricultural information is one of the important factors in agricultural production. Communication Information Technology (ICT) in the agricultural sector will lead to sustainable agriculture through the preparation of agricultural information that is timely, relevant in the decision-making process to increase its productivity. This study aimed to determine the effect of the Cyber extension and communication media on the innovation adoption in Nganjuk Regency. The study was conducted in Nganjuk Regency from June to September 2019, with a sample size of 110 people. The study was designed using SEM approach with the help of AMOS 21 application. The results showed the openness of farmers in Nganjuk Regency to the Cyber extension extension media had the highest score on the Cyber Extension extension media variable, this was due to ownership of communication equipment, selection of communication equipment types, availability of communication networks and high desire to find suitable information. WhatsApp communication media indicator had the highest score on the communication media variable, this was due to the communication media according to the needs of farmers in Nganjuk District, easy to use and able to reach broad communication. Cyber extension extension media and communication media influence the adoption of innovation, because appropriate extension media and communication media can accelerate the process of innovation adoption.